Geriatric Syndromes Predict Postdischarge Outcomes Among Older Emergency Department Patients: Findings From the interRAI Multinational Emergency Department Study. (April 2014) - Costa, Andrew P.; Hirdes, John P.; Heckman, George A.; Dey, Aparajit B.; Jonsson, Palmi V.; Lakhan, Prabha; Ljunggren, Gunnar; Singler, Katrin; Sjostrand, Fredrik; Swoboda, Walter; Wellens, Nathalie I.H.; Gray, Leonard C.; et al.
Abstract Objectives Identifying older emergency department (ED) patients with clinical features associated with adverse postdischarge outcomes may lead to improved clinical reasoning and better targeting for preventative interventions. Previous studies have used single‐country samples to identify limited sets of determinants for a limited number of proxy outcomes. The objective of this study was to identify and compare geriatric syndromes that influence the probability of postdischarge outcomes among older ED patients from a multinational context. Methods A multinational prospective cohort study of ED patients aged 75 years or older was conducted. A total of 13 ED sites from Australia, Belgium, Canada, Germany, Iceland, India, and Sweden participated. Patients who were expected to die within 24 hours or did not speak the native language were excluded. Of the 2, 475 patients approached for inclusion, 2, 282 (92.2%) were enrolled. Patients were assessed at ED admission with the interRAI ED Contact Assessment, a geriatric ED assessment. Outcomes were examined for patients admitted to a hospital ward (62.9%, n = 1, 436) or discharged to a community setting (34.0%, n = 775) after an ED visit. Overall, 3% of patients were lost to follow‐up. Hospital length of stay (LOS) and discharge to higher level of care was recorded for patients admitted to a hospital ward. Any ED or hospital use within 28 days of discharge was recorded for patients discharged to a community setting. Unadjusted and adjusted odds ratios (ORs) were used to describe determinants using standard and multilevel logistic regression. Results A multi‐country model including living alone (OR = 1.78, p ≤ 0.01), informal caregiver distress (OR = 1.69, p = 0.02), deficits in ambulation (OR = 1.94, p ≤ 0.01), poor self‐report (OR = 1.84, p ≤ 0.01), and traumatic injury (OR = 2.18, p ≤ 0.01) best described older patients at risk of longer hospital lengths of stay. A model including recent ED visits (OR = 2.10, p ≤ 0.01), baseline functional impairment (OR = 1.68, p ≤ 0.01), and anhedonia (OR = 1.73, p ≤ 0.01) best described older patients at risk of proximate repeat hospital use. A sufficiently accurate and generalizable model to describe the risk of discharge to higher levels of care among admitted patients was not achieved. Conclusions Despite markedly different health care systems, the probability of long hospital lengths of stay and repeat hospital use among older ED patients is detectable at the multinational level with moderate accuracy. This study demonstrates the potential utility of incorporating common geriatric clinical features in routine clinical examination and disposition planning for older patients in EDs.